OPTIMASI DESAIN COUNTER LEVER PADA GRAB BUCKET KAPASITAS 21 M^3 (50 SIKLUS/JAM) TERHADAP KETAHANAN LELAH - Gema Centra Adin (2023)
Ship unloader has the function of moving piles of coal from barges to land. Prolonged use may affect the mechanical properties of the ship unloader. Based on field data, the most frequent damage is to the grab bucket in the form of deformation and failure to break the counter lever. Optimization is carried out with the aim of increasing the fatigue life of the counter lever and facilitating the counter lever maintenance process when damage occurs. The optimization process is supported by analysis using the Ansys Workbench R1 software using the existing AISI 1020 material. The results of the analysis using the maximum load are the counter lever maximum stress, pin maximum stress, safety factor, and fatigue life respectively of 537,6 MPa, 418,48 MPa, 0,65104, 70.312 cycles. The addition of the ring uses a variety of new materials AISI 4130 and AISI 4340 on the pin with a spot weld connection as a solution to increase the safety factor. This variation of material was chosen because it has higher ultimate strength and has the same characteristics (Low Carbon Steel). The results of the analysis after optimization with 40 mm ring material AISI 4340 were chosen because they get an increase in life of ≥1,000,000 cycles without reducing the life of other components. With an increase in the safety factor to 1.2799, the optimization results are declared safe.